Challenges in the Development of Novel Treatment Strategies for Neuropathic Pain - Ossipov, Michael H. (The American Society for Experimental neuroTherapeutics, Inc., 2005)
Summary: Neuropathic pain might best be considered as a collection of various pain states with a common feature, that being symptoms suggestive of dysfunction of peripheral nerves. The development of therapeutic options for the treatment of neuropathic pain is complicated significantly by several factors. Neuropathic pain may arise from widely diverse etiologies such as physical trauma, disease, infection, or chemotherapy. Symptoms indicative of neuropathic pain may also arise in individuals with no evidence of any type of nerve trauma (idiopathic). Although neuropathic pain is a substantial health care issue, it is relatively uncommon and only occurs in a small fraction (<10%) of individuals with these initiating factors. Moreover, the efficacy of treatment protocols, even against the same type of symptoms, differ depending on the underlying initiating cause of the neuropathy. Although these observations strongly suggest that there are predisposing factors that may impart susceptibility to the development of neuropathic pain, no common predisposing factors or genetic markers have been satisfactorily identified. Because of these vagaries, treatment of neuropathic pain has been based on trial and error. However, recent progress in the understanding of neurophysiologic changes that accompany peripheral nerve dysfunction indicate that regulation of ion channels that maintain membrane potentials or generate action potentials may provide an important therapeutic approach. Neuropathic pain is accompanied by increased activity of peripheral nociceptors, which is produced in part by changes in levels of specific calcium and sodium channels. The identification of sodium and/or calcium channels subtypes that are expressed almost exclusively on nocicpetors may provide a way of regulating the activity of exaggerated nociceptor function without altering other sensory modalities. Thus, the selective targeting of ion channels may represent a viable therapeutic target for the management of the neuropathic pain state, regardless of etiology.